Investigation of the Damage Conditions of Reinforced Concrete Buildings and Steel Structures in Malatya Province Following the February 6, 2023 Kahramanmaraş - Atar, Muhammed; Ince, Ozan; Tas, Omer Faruk; Ozmen, Alper; Sayin, Erkut (Afet ve Acil Durum Yonetimi Baskanligi (AFAD), 2024)
On February 6, 2023, two earthquakes with a magnitude of Mw 7.7 occurred in the Pazarcik district of Kahramanmaraş, one at 04:17 and the second one at 13:24 in the center of Elbistan, with a magnitude of Mw 7.6. These two earthquakes happened 9 hours apart and significantly affected 11 cities. In this study, the damage conditions of reinforced concrete and steel structures in Malatya province were examined following the earthquakes that occurred in Kahramanmaraş on February 6, 2023. In the field study, mostly collapsed or heavily damaged structures were examined. Topics such as structural system and irregularities, material quality and application mistakes in construction processes are discussed. The field inspection revealed significant shortcomings in the implementation of earthquake regulations. More attention should be directed towards the design of the structural system and the quality of concrete materials, including aspects such as segregation in concrete, improper aggregate geometry, and insufficient concrete cover, in the design of earthquake-resistant structures. © 2024 Afet ve Acil Durum Yonetimi Baskanligi (AFAD). All rights reserved.
6 Şubat 2023 Kahramanmaraş Depremleri Sonrasi Malatya Ilinde Bulunan Betonarme Binalarin ve Çelik Yapilarin Hasar Durumlarinn Incelenmesi
Keywords: Earthquake damage; Kahramanmaraş earthquakes; Reinforced concrete structure; Steel structure